2021
DOI: 10.3390/pr9020204
|View full text |Cite
|
Sign up to set email alerts
|

Combined Approach to Analysis and Regulation of Thermodynamic Processes in the Energy Technology Complex

Abstract: The purpose of this work is to increase the theoretical and methodological approaches to value and regulate the dynamics of management processes. Application of these dynamics is implemented via methods of improving the quality of management of complex energy technology systems in the organization of recycling processes. As a result of the research, a technological model of a rotary kiln with a division into separate sections corresponding to the combustion zones for the production of cement clinker in recycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Toropov et al showed the possibility of organizing new methods in a new methodological framework. In addition, in [34], Toropov et al proposed to use the results of [33] for lowand medium-pressure thermal power equipment. It should be noted that the paper by Osintsev et al [35] shows the possibility of using the results of the work [33] in order to organize neural network control of combustion processes, including natural gas combustion.…”
Section: Experimental Datamentioning
confidence: 99%
“…Toropov et al showed the possibility of organizing new methods in a new methodological framework. In addition, in [34], Toropov et al proposed to use the results of [33] for lowand medium-pressure thermal power equipment. It should be noted that the paper by Osintsev et al [35] shows the possibility of using the results of the work [33] in order to organize neural network control of combustion processes, including natural gas combustion.…”
Section: Experimental Datamentioning
confidence: 99%
“…For example, Toropov et al [18] presented new methods for studying the operation of boiler units, and Toropov et al [19] showed the possibility of organizing new methods in a new methodological framework. In addition, Alabugin et al [20], propose to use the results of [19] for lowand medium-pressure thermal power equipment. It should be noted that the paper by Osintsev et al [21] shows the possibility of using the results of the work [19] in order to organize neural network control of combustion processes, including natural gas combustion.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the scale of their transformation into educational and scientific 4.0 complexes is growing with universities that are distinguished by a high degree of globalization of education and the use of new educational methods using big data methods. Currently, a number of researchers have recognized the need for the use of training digital simulators (doubles) in virtual or real cognitive methods to apply the data science approach for solving practical problems of the post-industrial economy and energy [19,20]. In such a digital economy, it is necessary to use open educational platforms based on large databases [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This makes it necessary to use special mathematical software, used, for example, to represent the processes of signal transmission. Such features determine the additional use of tools for deeper analysis and digital modeling of Data Science processes [7,20]. It is based on providing real-time control and regulation using deep machine learning neural network algorithms using artificial intelligence.…”
Section: Wind Power Plantmentioning
confidence: 99%
See 1 more Smart Citation